Severe acute respiratory syndrome coronavirus (SARS-CoV-2) is not detected in the vagina: A prospective study - Takmaz, Ozguc; Kaya, Eren; Erdi, Burak; Unsal, Gozde; Sharifli, Pari; Agaoglu, Nihat Bugra; Ozbasli, Esra; Gencer, Serap; Gungor, Mete (PUBLIC LIBRARY SCIENCE, 2021)
Objective To determine whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is present in the vagina of women diagnosed with coronavirus disease-19 (COVID-19) pneumonia. Study design The study was conducted prospectively in a university affiliated hospital. Forty-one women of reproductive age whose nasopharyngeal PCR test were positive for SARS-CoV-2 and clinically diagnosed with pneumonia were included in the study. Vaginal swabs were obtained for SARS-CoV-2 PCR tests when the patients were admitted to the inpatient service before pneumonia treatment was initiated. Results Vaginal swab samples of 38 patients were analysed with SARS-CoV-2 PCR tests. None of the vaginal swabs were positive for SARS-CoV-2. Conclusions SARS-CoV-2 does not infect the vagina of women diagnosed with SARS-CoV-2 pneumonia.